Assessment of the Development Potential of Shallow Geothermal Energy Heating and Cooling Projects in Southern China Based on Whole-Lifecycle Methodology - Yiqirui Deng; Zhi Yao; Mengyu Chen; Yu-Jie Hu (Energies)
The development of shallow geothermal energy projects in southern China can meet the demand for regional heating and cooling energy and carbon emission reduction. However, research on constructing evaluation models for the development potential of shallow geothermal energy projects needs to be expanded. Therefore, this study adopted a hierarchical analysis method to construct a project development potential evaluation model based on the four aspects of resource endowment, economic evaluation, environmental impact, and social support for the shallow geothermal energy heating and cooling project (vertical buried pipe heat exchange system) in southern China and carried out case application and evaluation verification. The results of the study show that: (a) the weights of the four primary indicators for evaluating the development potential of shallow geothermal energy projects in southern China were resource endowment (0.3960) > economic evaluation (0.2847) > social support (0.1725) > environmental impact (0.1468); (b) four secondary indicators, namely heat exchange performance, incentive and supportive policies, geotechnical and thermal-physical parameters, and groundwater conditions, were more important; (c) the case evaluation score was 6.2911, and case application and evaluation verification were carried out. For projects with good potential for investment, contrary to the single financial NPV index evaluation results, our results are more in line with the actual operation results of the project. Thus, this evaluation system can provide a more comprehensive reference for shallow geothermal energy development and investment decision-making.